The research of the adsorption properties of 5-(phenoxymethylene)-4-r-3-alkylthio-1,2,4-triazoles with highperformance liquid chromatography-mass-spectrometry - Kucheryavyi, Yu. M.; Lihnenko, A. V.; Lihnenko, Yu. V.; Кучерявий, Юрій Миколайович; Лихненко, А. В.; Лихненко, Ю. В. (Запорізький національний університет, 2016)
An important aspect of searching new biologically active molecules is prediction of pharmacokinetic parameters for these compounds. Before inserting a needful pharmacophore group into the structure, to achieve a certain type of biological activity, it’s necessary to define and calculate the possible adsorption properties of the molecule. The speed and efficiency of the molecule transport ability will depend on its bioavailability, therapeutic dose, side effects, etc. The lyophility is one of the important factors which determines the adsorption capacity of not watersoluble substances. And lyophility is also an affinity measure of organic substances to lipids.
Keywords: тези